Utilization of health care services in Varanasi District, India – A geographical analysis - Praveen Kumar Rai; Mahendra Singh Nathawat (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
People are not just spread unevenly across the Earth’s surface; they also differ along many demographic and socioeconomic lines that affect their accessibility to health care services with far reaching policy and planning implications. The main objective of this paper is to estimate the utilization pattern of health care services in the Varanasi district of India. Primary data pertaining to the utilization of health care facilities were collected from 800 respondents of 16 selected villages of rural Varanasi and analyzed with the SPSS statistical software. Varanasi City proper was not considered for this purpose because the presence and functioning of many private and government hospitals here meant that people were able to avail themselves of a fairly good range of healthcare facilities in comparison to people residing in the rural areas. Results of the findings revealed a high level of awareness among the local public of both the existence of the health care centres (78% ) and the type of health services they provided (75% for vaccination; 70% mother-child health services; 62% family planning; and 52% general treatment). Despite such high levels of awareness only 25% of them were satisfied with all the health care services provided by the centres (PHC), 60% were only partially satisfied and the remaining 14% were not satisfied at all. These findings thus underline the geographical disparities between urban and rural Varanasi.